Raton's roots sink deep in New Mexico's history Lynette Hunnicutt - Hunnicutt, Lynette (Raton, NM Raton Range, 1983)
Article on Raton's roots
Master List item # 35
File location is in the Raton File Cabinet
Keywords: Wooton, Richens Lacy; Pace, George; Long, S.H.; Gardiner, James T; Santa Fe Railroad; Blossburg Coal Mine; Raton Coal and Coke Company; Old Gardiner Mine; Rocky Mountain & Pacific Railroad; Local History; Railroad; Coal Mining; Willow Springs, New Mexico; Raton, New Mexico; Atchison, Kansas; Topeka, Kansas; Santa Fe, New Mexico; Denver, Colorado; Huerfano, Colorado; Cimarron, New Mexico